Answer:
Explanation:
4. x=2.25,−2.25
Step 1: Add 81 to both sides. Step 2: Divide both sides by 16.
16x2−81+81=0+81 16x^2/16 = 81/16
16x^2 x^2 = 81/16
Step 3: Take square root.
x = ± \sqrt(x)81/16
x=2.25,−2.25
5. x=3 or x=−6
Step 1: Subtract 18 from both sides.
x2+3x−18=18−18
x2+3x−18=0
Step 2: Factor the left side of the equation.
(x−3)(x+6)=0
Step 3: Set factors equal to 0.
x−3=0 or x+6=0
x=3 or x=−6
6. x = 1/5
Step 1: Simplify both sides of the equation.
4x+11x=3
(4x+11x)=3 (Combine Like Terms)
15x=3
Step 2: Divide both sides by 15.
15x/15 = 3/15
x = 1/5
7. x = 8, x = -5/2
Using the zero factor principle if ab = 0 then a = 0 or b = 0
x-8=0 or 2x+5=0
Add eight to both sides
x-8+8 = 0+8
simplify
x = 8
Subtract 5 from both sides
2x+5-5=0-5
simplify
2x - 5
divide both sides by 2
2x/2 = -5/2
x = -5/2